(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: The topic of death is still little discussed during undergraduate courses in health, both in theory and in practice, as the curriculum does not adequately address this issue in preparing the professional future because it emphasizes life and mitigates the death. Objective: The aim of the qualitative research is to investigate the current meaning of death according to nursing students. Methods: It was carried out at the Nursing School of Federal University of Juiz de Fora from March to April 2015; participants comprised ten undergraduate Nursing students enrolled at eighth semester of the aforementioned course. Open interviews were performed with; participants, whose statements were recorded, transcribed and later grouped by meaning proximity. Results: Comprehensive analysis of participants’ statements enabled the development of two units, namely: knowledge about death and meaning of death. Results have shown that Nursing students bear their own religious issues, which significantly influence their experiences, as well as biological and distress issues. Besides, they do not feel prepared to deal with death in the epistemological context. Conclusion: Therefore, it is crucial for Nursing students to acquire further knowledge about this subject in order to help improving their confidence, as well as better understanding and perceiving death.